RESEARCH ON THE GEAR OF SHEARER’S CUTTING PART BASED ON MFC-ANNS - ZHAO LiJuan; LI MingHao (Jixie qiangdu)
In order to do innovative design and study for the gears of shearer’s cutting part,the rigid-flexible coupling model of rocker system was established to study the thermal equilibrium procedure of the gear system,the temperature load and boundary conditions were determined and the different working conditions load files which were output by MSCAdams were loaded.Temperature-structure coupling analysis of the gears were studied by ANSYS,the temperature field nephogram and the structure coupling analysis nephogram of the gears were obtained. Combining MFC with ANNs could predict shearer ’s kinematics parameters when the gears was reliable operation,the prediction error reach 5. 6538 × 10- 6,the research results provides a unequivocal quantitative basis for the design and optimization of gear type parts which could improve this type of parts’ functional reliability effectively,this method has instruction significance to practical shearer’s productions.